Recent progress in cassava agronomy research in Thailand - Sittibusaya, C.; Tiraporn, C.; Tongglum, Anuchit; Cenpukdee, U.; Vichukit, Vichan; Jantawat, Somjate; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1995)
The paper reviews the available data and current activities on agronomic aspects of cassava in Thailand. These activities were carried out by various national research programs in collaboration with CIAT during 1990-1993. The review shows that the inherent fertility of cassava soils has been depleted due to long-term cassava monocropping without sufficient replacement of plant nutrients, and from degradative processes of soil erosion, root yields due to nutrient stress, water stress and top soil loss by erosion. Variability in production and income is a major characteristic of cassava cropping in Thailand. The challenge remains for research to take an integrated approach, involving all aspects of soil water, fertility and crop management in the program. Topics discussed include: a) erosion control; b) cropping practices; c) integrated plant nutrition systems; d) soil fertility evaluation; and e) efficient use of fertilizers